The Political Integration of Immigrants: How Pre- and Postmigration Contexts Matter - Jörg Dollmann (Journal of International Migration and Integration, 2021)
This study examines the political integration of immigrants in Germany and asks whether immigrants and their descendants show similar rates of political participation and expression of political attitudes as the population without an immigrant background. Furthermore, the study focusses on the pre- and postmigration context of immigrants and analyses whether immigrants differ in their level of political integration depending on (1) whether they come from more or less authoritarian regimes and (2) whether they have experienced discrimination in the receiving context. Using data from CILS4EU-DE, with a large representative sample of (children of) immigrants and non-immigrants in Germany, we observe differences in the political integration between immigrants and non-immigrants only on the attitudinal level, with immigrants showing lower levels of political trust but also slightly higher levels of satisfaction with the democratic system in Germany. When focussing on the effects of the pre- and the postmigration context, we observe differential results for the behavioural and attitudinal dimension: when immigrants stem from more authoritarian countries as well as when they have experienced more discrimination in the receiving context, this seems to mobilise respondents with respect to their political behaviour; however, it results in lower levels of political integration on the attitudinal dimension.
Keywords: 300; Political integration; Political participation; Political attitudes; Immigrants; Discrimination; Premigration context; Germany